Konsep Kesetaraan Gender dalam Ritual Pa’bannetauan Perkawinan - Maran, Alfian Mela; Marselius Sampe Tondok (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2024)
This study discusses the division of gender roles in the culture of Mamasa, West Sulawesi, focusing on the Pa'bannetauan ritual related to marriage and childbirth. The study finds that the bilateral kinship system in Mamasa allows for an equitable division of roles between men and women, supporting gender equality. Although there is freedom in choosing a partner, strict customary rules must still be followed, including offerings and agreements between both families. These findings are compared with patrilineal and matrilineal kinship systems in other cultures, showing that the bilateral system in Mamasa better supports gender equality. The article concludes that the customary norms in Mamasa can serve as an example of how traditions can support gender equality and justice in society.